Celebrating Howard Watkins' 40th Birthday in Backyard - Watkins, Howard::::::::: (1987)
Frances Kamp, Vickie Leet, Peggy Sanders, Leslie Prusia, Howard Watkins, Laurie Tidyman-Jones and Tim Tidyman-Jones at hors-d'oevre table at covered patio